FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI MAHASISWA PENDIDIKAN TEKNIK BANGUNAN UNTUK MENJADI GURU - Alvin Rivaldi; Daryati; Rosmawita Saleh (LPPM Universitas Negeri Jakarta, 2020)
This study aims to obtain an overview of the factors that influence the motivation of active students of the Building Engineering Education Faculty of Engineering, State University of Jakarta. This research is calculated from June to July 2019. This research was conducted on students of the Building Engineering Education Faculty of Engineering, State University of Jakarta class of 2016, 2017 and 2018, using descriptive methods that are quantitative. The results obtained from this research are the factors that influence the motivation of active students of Building Engineering Education, Engineering Faculties, Jakarta State University, class 2016, 2017 and 2018, tend to be high, it's just that the desire factor is still sufficient or moderate. These factors include: Desire (59.45%); Needs (76.88%); Personality (76.39%); Ability (68.87%); Welfare (66.77%); Social Environment (64.68%).